2021
DOI: 10.1039/d1ew00389e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes among non-volatile disinfection by-products between drinking water treatment and consumer taps

Abstract: The formation of disinfection by-products (DBPs) during drinking water treatment has been associated with various health concerns but the agents, i.e., the DBPs that cause these health concerns, are still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…DWTPs 3, 4, and 5 provide drinking water to the same city. The DBP mix in the finished water of DWTP may change in the distribution system due to dilution, hydrolysis, or enhanced contact time with a disinfectant . Therefore, additional samples were collected from two entry points to a drinking water distribution network and two drinking water storage reservoirs of this city (Figure S26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DWTPs 3, 4, and 5 provide drinking water to the same city. The DBP mix in the finished water of DWTP may change in the distribution system due to dilution, hydrolysis, or enhanced contact time with a disinfectant . Therefore, additional samples were collected from two entry points to a drinking water distribution network and two drinking water storage reservoirs of this city (Figure S26).…”
Section: Resultsmentioning
confidence: 99%
“…The DBP mix in the finished water of DWTP may change in the distribution system due to dilution, hydrolysis, or enhanced contact time with a disinfectant. 40 Therefore, additional samples were collected from two entry points to a drinking water distribution network and two drinking water storage reservoirs of this city (Figure S26). At these locations much closer to the consumer taps, total HANSAs were up to 2-fold higher (30−50 ng/L) than those produced at DWTPs.…”
Section: Structural Confirmation and Quantificationmentioning
confidence: 99%
“…The greater prevalence of polyunsaturated fatty acids suggests that oleic acid 9,10-chlorohydrins may represent a minor component of a larger chlorohydrin pool. While this predictive approach provides one path for characterizing high-molecular weight DBPs, it only complements the need for nontargeted analytical approaches that identify partially degraded biomolecular components. …”
Section: Resultsmentioning
confidence: 99%
“…One approach applies nontargeted high-resolution mass spectrometry, which avoids prior assumptions about these structures. Such studies have identified hundreds of halogenated elemental formulae, although defining specific structures is laborious. Recognizing that DOM precursors feature aromatic structures, other researchers have developed novel mass spectrometry techniques to demonstrate the occurrence of halogenated aromatic byproducts (e.g., halobenzaldehydes). …”
Section: Introductionmentioning
confidence: 99%
“…Solid phase extraction (SPE) is commonly used as a pretreatment step before direct infusion (DI) into HRMS as it can enrich a broad range of organic compounds and efficiently remove inorganic constituents. 6,7,22–26 In general, reversed-phase (RP) type SPE sorbents facilitate the recovery of nonpolar and polar compounds, 21,27–29 whereas the most polar compounds can also be overlooked due to their incomplete recovery during the SPE process. 20 In addition, the traditional SPE-DI analysis with HRMS cannot be used to obtain isomeric information of DOM and DBPs due to the large structural diversity of both classes of compounds.…”
Section: Introductionmentioning
confidence: 99%